2010
DOI: 10.1016/j.carbpol.2010.02.022
|View full text |Cite
|
Sign up to set email alerts
|

In vivo degradation of banana starch: Structural characterization of the degradation process

Abstract: a b s t r a c tThis work reports the first ultrastructural investigation into the degradation process that starch granules isolated from bananas (cv. Nanicão) undergo during ripening. Starch granules from green bananas had a smooth surface, while granules from ripe bananas were more elongated with parallel striations, as revealed by CSLM and SEM. AFM images revealed that the first layer covering the granule surface is composed of a hard material and, as degradation proceeds, hard and soft regions seem to be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
1
10

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 55 publications
4
27
1
10
Order By: Relevance
“…As reported in that table, BS showed a mean particle size of 33.4 ± 0.18 μm, with DI of 0.24. These values agree with previous reports on green banana starch, with mean particle sizes ranging from 0.9 to 100 μm and low DI values . When nanoprecipitation is carried out, mean particle size decreases considerably, with BSNps and CABNps showing diameters of 120 ± 0.05 and 220 ± 0.03 nm, respectively.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…As reported in that table, BS showed a mean particle size of 33.4 ± 0.18 μm, with DI of 0.24. These values agree with previous reports on green banana starch, with mean particle sizes ranging from 0.9 to 100 μm and low DI values . When nanoprecipitation is carried out, mean particle size decreases considerably, with BSNps and CABNps showing diameters of 120 ± 0.05 and 220 ± 0.03 nm, respectively.…”
Section: Resultssupporting
confidence: 91%
“…starch, with mean particle sizes ranging from 0.9 to 100 μm and low DI values. 33,34 When nanoprecipitation is carried out, mean particle size decreases considerably, with BSNps and CABNps showing diameters of 120 ± 0.05 and 220 ± 0.03 nm, respectively. It has been reported that chemical modification of starch nanoparticles, like acetylation, can lead to increased particle size, due to an increase in the intermolecular hydrogen bonds between starch nanoparticles and water.…”
Section: Resultsmentioning
confidence: 99%
“…The granule size distribution may provide a better understanding of the behavior of the starch granules during processing. Peroni‐Okita et al reported in banana starch a D [ v ,0.5] of the distribution peak of 29 µm, indicating that 10% of the granules had a diameter of 10 µm and 90% of 49.6 µm. In this study, it was found that 10 and 90% of Enano and Morado granules had an approximate diameter of 5 and 70 µm, respectively, while Macho and Valery had an approximate diameter of 8 and 128 µm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The filtrate drops into the low level of the box (8) and flows out through the flange (10). The flange (10) is connected at the pipe (11) to the flange (13) that feeds the second box (14) with the sieve US 200 (15). The filtrate flows out onto the surface of the sieve (15).…”
Section: Process Descriptionmentioning
confidence: 99%